2022
DOI: 10.1155/2022/4558159
|View full text |Cite
|
Sign up to set email alerts
|

CXC Chemokines in the Pathogenesis of Pulmonary Disease and Pharmacological Relevance

Abstract: Chemokines and their receptors play important roles in the pathophysiology of many diseases by regulating the cellular migration of major inflammatory and immune players. The CXC motif chemokine subfamily is the second largest family, and it is further subdivided into ELR motif CXC (ELR+) and non-ELR motif (ELR-) CXC chemokines, which are effective chemoattractants for neutrophils and lymphocytes/monocytes, respectively. These chemokines and their receptors are expected to have a significant impact on a wide r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 157 publications
(258 reference statements)
0
8
0
Order By: Relevance
“…A previous study showed that CD69 is one of the lung-resident markers [ 39 ]. CXCL12, the ligand of CXCR4, is abundant in the lung [ 40 ] and the CXCR4/CXCL12 axis was important in lung injury/fibrosis [ 41 ]. Thus, CD69, CXCR4 and other markers expressed by Tph cells could promote the chemotaxis of Tph cells to the lung in ABPA coordinately.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study showed that CD69 is one of the lung-resident markers [ 39 ]. CXCL12, the ligand of CXCR4, is abundant in the lung [ 40 ] and the CXCR4/CXCL12 axis was important in lung injury/fibrosis [ 41 ]. Thus, CD69, CXCR4 and other markers expressed by Tph cells could promote the chemotaxis of Tph cells to the lung in ABPA coordinately.…”
Section: Discussionmentioning
confidence: 99%
“…The Tph cells of ABPA patients expressed chemokines for neutrophils such as CXCL2, CXCL3 and CXCL8. Studies show that they are involved in the allergic inflammation and could exaggerate type 2 response [ 41 43 ]. Besides, CXCL8 might increase the bronchoconstriction by stimulating airway smooth muscle cells in cystic fibrosis and asthma [ 42 ], both of which are major concomitant diseases of ABPA.…”
Section: Discussionmentioning
confidence: 99%
“…MIG and IP-10 were the most effective diagnostic markers for differentiating between asymptomatic/mildly symptomatic COVID-19 patients and COVID-19 patients with pneumonia without respiratory failure. Both chemokines belong to the CX subfamily and the non-ELR subgroup ( 36 , 37 ). Non-ELR chemokines lack the ELR (Glu-Leu-Arg) motif, and they act as chemoattractants and activators of monocytes, dendritic cells, lymphocytes (T, B, and NK cells), basophils and eosinophils, without angiogenic potential ( 38 , 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…upregulation of the bacterially induced inflammatory cytokine C-X-C motif chemokine ligand 5 (CXCL5) [1,2].…”
mentioning
confidence: 99%
“…Smoking has a lasting impact on the immune system, including alterations in adaptive immune response cytokine production. Specifically, active smoking is associated with an upregulation of the bacterially induced inflammatory cytokine C-X-C motif chemokine ligand 5 (CXCL5) [1, 2].…”
mentioning
confidence: 99%